Compressive Strength Characteristics of Concrete Modified With Treated High-Density Polyethylene - Anum, Iorwuese; Job, Fredrick (CSID Journal of Infrastructure Development, 2021)
Waste plastic materials are typical wastes of interest to researchers and are arguably the most common forms of waste, especially in African cities. The reuse of plastic waste in concrete matrices has the potentials to contribute to the development of sustainable concrete likely to conserve resources and prevent pollution. However, the inclusion of plastics in concrete has been reported to have a negative impact on its compressive strength behaviour. This research is aimed at ameliorating this negative impact through pulverisation and chemical treatment of High-Density Polyethylene (HDPE) before its use as an admixture for concrete production. Concretes of Grades M25 and M50 were prepared using (150 x150 x 150) mm steel moulds, adopting the BRE mix design method. The concrete mix was modified with pulverised High-Density Polyethylene (HDPE) treated with 20% hydrogen peroxide at (0, 0.25, 0.5, 0.75, and 1%) by weight of cement. Hydroplast-500, a superplasticizer was used throughout the study in order of 1000litres/50kg by weight of cement. A constant water/cement ratio of 0.4 and 0.36 was adopted for requisite workability for Grades M25 and M50 concretes respectively. After 7, 28, and 90 days of curing in water, the concrete cubes were dried and tested for their compressive strengths. Results obtained showed that at HDPE content beyond 0.5%, restrained hydration takes negative effects on the concrete. It was also shown that the designed compressive strengths of the tested samples were satisfactorily met in all cases indicating improvement in the compressive behaviour of the samples.  Based on the findings of this study, it was recommended that treated pulverised HDPE could be used as an admixture in concretes without compromising their compressive strengths.